Proyecto de factibilidad para la creación de una empresa de fabricación de vigas electrosoldadas tipo i, y su comercialización en la ciudad de Loja - Piedra Cartuche, Galo Augusto (2016)
his project focuses on one aspect of growth that has mostly the construction industry in the city of Loja and it is for this reason that we must embark on projects which help significantly encentrar urgent solutions to the population They want to make a building of any kind using materials like welded beams type I. That is why in this research has emerged as main objective the creation of a "FEASIBILITY PROJECT FOR THE CREATION OF A MANUFACTURING COMPANY ELECTROSOLDADAS TYPE I BEAMS, AND MARKETING IN THE CITY OF LOJA" which gave rise the thesis topic, which is the first item of work. The thesis project is feasible to do it as well demonstrated in all studies and contained in this paper. The project is welcome as this study demonstrates the market, where it was found that there is unmet demand, which is estimated at 838 656 welded beams for builders in the city of Loja. In the technical study it was determined that the company working at 100% capacity could produce 41,600 beams welded to the builders in the city of Loja. According to the organizational study, the new company will be established as a limited liability company. The total investment for the implementation of the new company is $ 236,717.77 whose source of financing of the initial investment will be made with foreign capital and a credit will be made to the National Finance Corporation, worth $ 50,000.00 corresponding 21% of the total investment and domestic capital to be held by providing partners with a total value of $ 186,717.77, which corresponds to 79% of the total investment. The breakeven point for the first year of life of the project is at a standstill as the occupying 30.42% of the Prompted capacity and has revenues of $ 231,277.31. The financial analysis shows that the project is feasible as the case NPV that was worth $ 685,264.26, the project IRR is 57.43%, the recovery period Capital will in 2 years, 1 month and 6 days, the cost / benefit ratio is 1.36 and sensitivity analysis indicates that the project reaches the point of sensitivity when costs are increased by 20.38% and decrease revenue by 15.17%. However for reasons of market introduction will work with 80% for the first year.